Answer:
that sucks and lol
Step-by-step explanation:
that's how I feel
the highest batting average is of Ed's and that is 0.350 .
<u>Step-by-step explanation:</u>
Here we have , Make, Dan, Ed, and summer played together on a baseball team. Mike’s batting average was 0.349, dan’s was 0.2, Ed’s was 0.35, and sy’swas 0.299. We need to find Who had the highest batting average . Let's find out :
According to question we have following parameters as :
![Mike = 0.349\\Dan's=0.200\\Ed's=0.350\\Sy'swas=0.299](https://tex.z-dn.net/?f=Mike%20%3D%200.349%5C%5CDan%27s%3D0.200%5C%5CEd%27s%3D0.350%5C%5CSy%27swas%3D0.299)
Arranging these data from decreasing to increasing order we get :
⇒ ![0.200](https://tex.z-dn.net/?f=0.200%3C0.299%3C0.349%3C0.350)
⇒ ![(Dan's)0.200](https://tex.z-dn.net/?f=%28Dan%27s%290.200%3C%28Sy%27swas%290.299%3C%28Mike%27s%290.349%3C%28Ed%27s%290.350)
Therefore , the highest batting average is of Ed's and that is 0.350 .
Answer:
I think it is 2 one
Step-by-step explanation:
Answer:
6,3,-3, and -6
Step-by-step explanation:
You just replace y with the given numbers, then solve for x
Answer:
![(-1)+(-3)=-4](https://tex.z-dn.net/?f=%28-1%29%2B%28-3%29%3D-4)
Step-by-step explanation:
We were originally on -1.
But we jumped to -4.
-4 is 3 spaces to the left of -1.
In other words, we subtract 3 into -1.
Another way of saying this is that we added -3 to -1.
Therefore, our equation is:
![(-1)+(-3)=-4](https://tex.z-dn.net/?f=%28-1%29%2B%28-3%29%3D-4)